Bonded laminated iron core for stator, method for manufacturing the same, and rotating electrical machine

By providing part of the bonding portion in the bonded laminated iron core for stator and bonding with a double-dose acrylic adhesive, the problem of poor iron loss suppression effect of rotating electric machines in the prior art is solved, and more efficient iron loss control and productivity improvement are achieved.

CN113228468BActive Publication Date: 2025-04-11NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980082449.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-17
Filing Date
2019-12-17
Publication Date
2025-04-11
Estimated Expiration
2039-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress iron losses of rotating electric machines, especially in the lamination process of rotor cores.

Method used

A stator-based adhesive laminated iron core is used, which is made of a plurality of electromagnetic steel plates, and a partial bonding portion is provided between the steel plates adjacent to the lamination direction, and bonding is performed using a double-dosage acrylic adhesive. The adhesive consists of an acrylic compound, an oxidizing agent and a reducing agent, and cures rapidly at room temperature.

Benefits of technology

By reducing curing shrinkage and thermal expansion stress, distortion of the electromagnetic steel plate is suppressed, thereby effectively reducing iron loss of the rotating motor, and improving the productivity of the bonded laminated iron core for stator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113228468B_ABST
    Figure CN113228468B_ABST
Patent Text Reader

Abstract

The present invention provides a stator bonded laminated core that can suppress iron loss of a rotating electric machine and has relatively excellent productivity. The stator bonded laminated core includes a plurality of electromagnetic steel plates and a bonding portion, wherein the plurality of electromagnetic steel plates are stacked on each other and covered on both sides with an insulating film, the bonding portion is arranged between electromagnetic steel plates adjacent to each other in the stacking direction, and the electromagnetic steel plates are bonded to each other, and all groups of electromagnetic steel plates adjacent to each other in the stacking direction are bonded by the bonding portion, and the adhesive forming the bonding portion includes an acrylic compound, an oxidizing agent, and a reducing agent, and is a two-component acrylic adhesive (SGA) in which a part of the acrylic compound and the oxidizing agent are mixed in a first component, and the remaining part of the acrylic compound and the reducing agent are mixed in a second component, and the bonding portion is partially provided between the electromagnetic steel plates adjacent to each other in the stacking direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a bonded laminated core for a stator, a method for manufacturing the same, and a rotating electrical machine.

[0002] This application claims priority based on Japanese Patent Application No. 2018-235869 filed in Japan on December 17, 2018, and the contents are incorporated herein by reference. Background Art

[0003] Conventionally, as an iron core used in a rotating electric machine, a laminated iron core is known in which a plurality of electromagnetic steel plates are laminated on each other. The plurality of steel plates are joined by welding, bonding, riveting, or the like.

[0004] Patent Document 1 discloses a technique of using a two-component curing adhesive in a lamination process of a plurality of rotor steel plates constituting a rotor core.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-046442 Summary of the invention

[0008] Technical problem to be solved by the invention

[0009] However, in the rotor core obtained by the technique of Patent Document 1, the iron loss of the rotating electric machine cannot be sufficiently suppressed.

[0010] An object of the present invention is to provide a stator bonded laminated iron core capable of suppressing iron loss of a rotating electric machine and having excellent productivity, a method for manufacturing the stator bonded laminated iron core, and a rotating electric machine including the stator bonded laminated iron core.

[0011] Solutions to technical problems

[0012] One embodiment of the present invention has the following aspects.

[0013] [1] A bonded laminated core for a stator, comprising:

[0014] A plurality of electromagnetic steel sheets are stacked one on another and both sides are covered with insulating films, and

[0015] a bonding portion disposed between the electromagnetic steel sheets adjacent to each other in a stacking direction and bonding the electromagnetic steel sheets to each other;

[0016] All groups of the electromagnetic steel sheets adjacent to each other in the stacking direction are bonded by the bonding portion;

[0017] The adhesive forming the bonding portion comprises an acrylic compound, an oxidizing agent, and a reducing agent, and is a two-part acrylic adhesive in which a portion of the acrylic compound and the oxidizing agent are mixed in a first part, and the remaining portion of the acrylic compound and the reducing agent are mixed in a second part;

[0018] The bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction.

[0019] [2] The stator bonded laminated core of [1], wherein:

[0020] The acrylic compound comprises at least one selected from the group consisting of methyl methacrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate;

[0021] The methyl methacrylate, the phenoxyethyl methacrylate, the 2-hydroxyethyl methacrylate, and the 2-hydroxypropyl methacrylate are present in an amount of 0 to 50% by mass, 0 to 50% by mass, and 0 to 50% by mass, respectively, relative to the total mass of the acrylic adhesive.

[0022] [3] A bonded laminated core for a stator, comprising:

[0023] A plurality of electromagnetic steel sheets are stacked one on another and both sides are covered with insulating films, and

[0024] a bonding portion disposed between the electromagnetic steel sheets adjacent to each other in a stacking direction and bonding the electromagnetic steel sheets to each other;

[0025] All groups of the electromagnetic steel sheets adjacent to each other in the stacking direction are bonded by the bonding portion;

[0026] The adhesive forming the bonding portion is an acrylic adhesive containing an acrylic compound;

[0027] The bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction.

[0028] [4] The bonded laminated core for a stator as described in [3], wherein:

[0029] The acrylic adhesive is an anaerobic adhesive.

[0030] [5] The bonded laminated core for a stator as described in [3], wherein:

[0031] The acrylic compound is cyanoacrylate.

[0032] [6] The bonded laminated core for a stator according to any one of [1] to [5], wherein:

[0033] The acrylic adhesive further includes an elastomer.

[0034] [7] The stator bonded laminated core of [6], wherein:

[0035] The elastomer comprises acrylonitrile-butadiene rubber;

[0036] The acrylonitrile-butadiene rubber is contained in an amount of 1 to 20% by mass based on the total mass of the acrylic adhesive.

[0037] [8] The bonded laminated core for a stator according to any one of [1] to [7], wherein:

[0038] The bonding area ratio of the bonding portion between the electromagnetic steel sheets to the electromagnetic steel sheets is 20 to 80%.

[0039] [9] A method for manufacturing a bonded laminated core for a stator according to [1], wherein:

[0040] After applying the first and second agents of the acrylic adhesive to a portion of the surface of the electromagnetic steel sheet at room temperature, the adhesive is overlapped and pressure-bonded to another electromagnetic steel sheet, and the bonding portion is formed repeatedly.

[0041]

[10] The method for manufacturing a stator bonded laminated core according to [3], wherein:

[0042] After applying the acrylic adhesive to a part of the surface of the electromagnetic steel sheet at room temperature, the sheet is overlapped and pressure-bonded to another electromagnetic steel sheet, and the bonding portion is formed repeatedly.

[0043]

[11] A rotating electrical machine comprising the bonded laminated core for a stator according to any one of [1] to [8].

[0044] Effects of the Invention

[0045] According to the present invention, it is possible to provide a bonded laminated iron core for a stator which can suppress the iron loss of a rotating electric machine and has excellent productivity, a method for manufacturing the same, and a rotating electric machine including the bonded laminated iron core for a stator. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a cross-sectional view of a rotating electrical machine including a bonded laminated core for a stator according to an embodiment of the present invention.

[0047] Figure 2 This is a side view of the same stator laminated core.

[0048] Figure 3 yes Figure 2AA cross-sectional view of the same stator is a diagram showing an example of a layout diagram of the bonding portion of the bonded laminated core.

[0049] Figure 4 It is a side view showing a schematic structure of a manufacturing apparatus for a stator bonded laminated core. DETAILED DESCRIPTION

[0050] Hereinafter, with reference to the accompanying drawings, a stator bonded laminated core according to an embodiment of the present invention and a rotating electrical machine having the stator bonded laminated core are described. In addition, in this embodiment, as a rotating electrical machine, an electric motor, specifically, an AC motor, more specifically, a synchronous motor, and more specifically, a permanent magnet field type motor are cited as an example for description. Such an electric motor is preferably used in, for example, electric vehicles, etc.

[0051] [First embodiment]

[0052] like Figure 1 As shown, the rotary electric machine 10 includes a stator 20, a rotor 30, a housing 50, and a rotating shaft 60. The stator 20 and the rotor 30 are accommodated in the housing 50. The stator 20 is fixed in the housing 50.

[0053] In the present embodiment, an inner rotor type in which the rotor 30 is located radially inside the stator 20 is adopted as the rotating electrical machine 10. However, an outer rotor type in which the rotor 30 is located outside the stator 20 may be adopted as the rotating electrical machine 10. In addition, in the present embodiment, the rotating electrical machine 10 is a 12-pole 18-slot three-phase AC motor. However, the number of poles, the number of slots, the number of phases, etc. may be appropriately changed.

[0054] The rotating electric machine 10 can be rotated at a rotation speed of 1000 rpm by applying an exciting current having an effective value of 10 A and a frequency of 100 Hz to each phase, for example.

[0055] The stator 20 includes a stator bonded laminated core (hereinafter referred to as a stator core) 21 and a winding (not shown).

[0056] The stator core 21 includes an annular core back 22 and a plurality of teeth 23. Hereinafter, the direction of the central axis О of the stator core 21 (or the core back 22) is referred to as the axial direction, the radial direction (the direction orthogonal to the central axis О) of the stator core 21 (or the core back 22) is referred to as the radial direction, and the circumferential direction (the direction circling around the central axis О) of the stator core 21 (or the core back 22) is referred to as the circumferential direction.

[0057] The core back 22 is formed in an annular shape in a plan view of the stator 20 viewed from the axial direction.

[0058] The plurality of teeth 23 protrude radially inward from the inner circumference of the core back 22 (radially toward the center axis O of the core back 22). The plurality of teeth 23 are arranged at equal angular intervals in the circumferential direction. In the present embodiment, 18 teeth 23 are provided at a center angle of 20 degrees with the center axis O as the center. The plurality of teeth 23 are formed into shapes and sizes that are equal to each other. Therefore, the plurality of teeth 23 have the same thickness dimension.

[0059] The winding is wound around the teeth 23. The winding may be concentratedly wound or distributedly wound.

[0060] The rotor 30 is arranged radially inward of the stator 20 (stator core 21 ). The rotor 30 includes a rotor core 31 and a plurality of permanent magnets 32 .

[0061] The rotor core 31 is formed in an annular shape (ring shape) arranged coaxially with the stator 20. The above-mentioned rotating shaft 60 is arranged in the rotor core 31. The rotating shaft 60 is fixed to the rotor core 31.

[0062] A plurality of permanent magnets 32 are fixed to the rotor core 31. In the present embodiment, a set of two permanent magnets 32 forms one magnetic pole. The plurality of sets of permanent magnets 32 are arranged at equal angular intervals in the circumferential direction. In the present embodiment, 12 sets (a total of 24) of permanent magnets 32 are arranged at a central angle of 30 degrees with the central axis O as the center.

[0063] In the present embodiment, an embedded magnet type motor is used as a permanent magnet field type motor. A plurality of through holes 33 are formed in the rotor core 31, which penetrate the rotor core 31 in the axial direction. The plurality of through holes 33 are provided corresponding to the arrangement of the plurality of permanent magnets 32. Each permanent magnet 32 ​​is fixed to the rotor core 31 in a state arranged in the corresponding through hole 33. The fixing of each permanent magnet 32 ​​to the rotor core 31 can be achieved, for example, by bonding the outer surface of the permanent magnet 32 ​​to the inner surface of the through hole 33 using an adhesive. In addition, as a permanent magnet field type motor, a surface magnet type motor may be used instead of an embedded magnet type motor.

[0064] The stator core 21 and the rotor core 31 are both laminated cores. Figure 2 As shown, a plurality of electromagnetic steel sheets 40 are stacked.

[0065] In addition, the stacking thickness (total length along the central axis О) of each of the stator core 21 and the rotor core 31 is set to 50.0 mm, for example. The outer diameter of the stator core 21 is set to 250.0 mm, for example. The inner diameter of the stator core 21 is set to 165.0 mm, for example. The outer diameter of the rotor core 31 is set to 163.0 mm, for example. The inner diameter of the rotor core 31 is set to 30.0 mm, for example. However, these values ​​are only examples, and the stacking thickness, outer diameter or inner diameter of the stator core 21, and the stacking thickness, outer diameter or inner diameter of the rotor core 31 are not limited to these values. Here, the inner diameter of the stator core 21 is based on the front end of the tooth portion 23 in the stator core 21. That is, the inner diameter of the stator core 21 is the diameter of a virtual circle inscribed in the front end of all the teeth 23.

[0066] Each electromagnetic steel sheet 40 forming the stator core 21 and the rotor core 31 is formed, for example, by punching an electromagnetic steel sheet as a base material. As the electromagnetic steel sheet 40, a known electromagnetic steel sheet can be used. The chemical composition of the electromagnetic steel sheet 40 is not particularly limited. In the present embodiment, a non-oriented electromagnetic steel sheet is used as the electromagnetic steel sheet 40. As the non-oriented electromagnetic steel sheet, for example, a non-oriented electrical steel strip of JIS C2552:2014 can be used.

[0067] However, a oriented electromagnetic steel sheet may be used instead of a non-oriented electromagnetic steel sheet as the electromagnetic steel sheet 40. As the oriented electromagnetic steel sheet, for example, a oriented electrical steel strip of JIS C2553:2012 may be used.

[0068] In order to improve the workability of the electromagnetic steel sheet and the iron loss of the laminated core, both surfaces of the electromagnetic steel sheet 40 are covered with an insulating film. As the material constituting the insulating film, the following materials can be used: (1) inorganic compounds, (2) organic resins, and (3) mixtures of inorganic compounds and organic resins. As inorganic compounds, for example, the following materials can be mentioned: (1) a complex of dichromate and boric acid, and (2) a complex of phosphate and silicon dioxide. As organic resins, epoxy resins, acrylic resins, acrylic styrene resins, polyester resins, silicone resins, and fluororesins can be mentioned.

[0069] In order to ensure the insulation performance between the electromagnetic steel sheets 40 stacked on each other, the thickness of the insulating film (the average thickness per one side of the electromagnetic steel sheet 40 ) is preferably set to 0.1 μm or more.

[0070] On the other hand, as the insulating film becomes thicker, the insulating effect becomes saturated. In addition, as the insulating film becomes thicker, the proportion of the electromagnetic steel sheet in the laminated core (fill factor) decreases, and the performance of the laminated core decreases. Therefore, the insulating film is preferably thinner within a range that can ensure the insulating performance. The thickness of the insulating film (the thickness of each single-sided electromagnetic steel sheet 40) is preferably 0.1 μm to 5 μm, and more preferably 0.1 μm to 2 μm.

[0071] As the thickness of the electromagnetic steel sheet 40 decreases, the improvement effect of the iron loss gradually saturates. In addition, as the electromagnetic steel sheet 40 becomes thinner, the manufacturing cost of the electromagnetic steel sheet 40 increases. Therefore, considering the improvement effect of the iron loss and the manufacturing cost, it is preferred that the thickness of the electromagnetic steel sheet 40 be set to 0.10 mm or more.

[0072] On the other hand, when the electromagnetic steel sheet 40 is too thick, it becomes difficult to perform press punching of the electromagnetic steel sheet 40. Therefore, in consideration of the press punching of the electromagnetic steel sheet 40, the thickness of the electromagnetic steel sheet 40 is preferably set to 0.65 mm or less.

[0073] In addition, when the electromagnetic steel sheet 40 becomes thicker, the iron loss increases. Therefore, considering the iron loss characteristics of the electromagnetic steel sheet 40, the thickness of the electromagnetic steel sheet 40 is preferably set to 0.35 mm or less, and more preferably 0.20 mm or 0.25 mm.

[0074] Considering the above point, the thickness of each electromagnetic steel sheet 40 is, for example, 0.10 mm to 0.65 mm, preferably 0.10 mm to 0.35 mm, and more preferably 0.20 mm or 0.25 mm. The thickness of the electromagnetic steel sheet 40 also includes the thickness of the insulating film.

[0075] like Figure 2 As shown, in the stator core 21, bonding portions 41 are partially provided between all groups of electromagnetic steel sheets 40 adjacent to each other in the stacking direction, and the bonding portions 41 bond these electromagnetic steel sheets 40 to each other. All groups of electromagnetic steel sheets 40 adjacent to each other in the stacking direction are stacked via the bonding portions 41 partially provided therebetween. The electromagnetic steel sheets 40 adjacent to each other in the stacking direction are not fixed to each other by other means (for example, rivets, etc.).

[0076] The bonding portion 41 bonds the electromagnetic steel sheets 40 adjacent to each other in the stacking direction. The bonding portion 41 is an adhesive that is solidified without being broken.

[0077] In order to stably obtain sufficient bonding strength, the thickness of the bonding portion 41 is preferably set to 1 μm or more.

[0078] On the other hand, when the thickness of the adhesive portion 41 exceeds 100 μm, the adhesive force will be saturated. In addition, as the adhesive portion 41 becomes thicker, the space factor will decrease, and the magnetic properties such as the iron loss of the stator core will decrease. Therefore, it is preferred that the thickness of the adhesive portion 41 is set to be greater than 1 μm and less than 100 μm, and more preferably, to be greater than 1 μm and less than 10 μm.

[0079] In the above description, the thickness of the adhesive portion 41 means the average thickness of the adhesive portion 41. The average thickness of the adhesive portion 41 can be adjusted by, for example, changing the amount of adhesive applied.

[0080] The average thickness of the bonding portion 41 is the average value of the entire laminated core. The average thickness of the bonding portion 41 hardly changes at the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average thickness of the bonding portion 41 can be determined by the average value of the values ​​measured at the upper end position of the laminated core and at least 10 positions in the circumferential direction.

[0081] The adhesive forming the adhesive portion 41 is a second generation acrylic adhesive (SGA). It can also be said that the adhesive portion 41 is composed of a cured product of SGA.

[0082] SGA contains an acrylic compound, an oxidizing agent, and a reducing agent.

[0083] The SGA in this embodiment is a two-part type, consisting of two parts, a first part and a second part. In addition, a part of the acrylic acid compound and the oxidizing agent among the above components are added to the first part, and the remaining part of the acrylic acid compound and the reducing agent are added to the second part. When these first parts are in contact with the second part, the acrylic acid compound is polymerized and cured due to the redox reaction.

[0084] Since the two-component SGA cures rapidly at room temperature (e.g., 20 to 30° C., or further, 20 to 25° C.), when forming the bonding portion 41, there is no need for a curing process such as a heating process in the case of a thermosetting adhesive, or a long-term holding process in the case of natural curing, and the stator core 21 can be manufactured with excellent productivity. SGA will be described in detail later.

[0085] Generally, when the adhesive is cured, curing shrinkage occurs. Due to the curing shrinkage, compressive stress and tensile stress are applied to the electromagnetic steel sheet 40. Since these stresses are applied to the electromagnetic steel sheet 40, distortion occurs. In particular, in the case of a thermosetting adhesive, the applied stress increases due to the difference in thermal expansion coefficient between the electromagnetic steel sheet 40 and the adhesive portion. The distortion of the electromagnetic steel sheet 40 increases the iron loss of the rotating electric machine 10. The distortion of the electromagnetic steel sheet 40 constituting the stator core 21 has a greater effect on the iron loss than the distortion of the steel sheet constituting the rotor core 31.

[0086] In this embodiment, since the adhesive portion 41 is partially provided, the stress applied to the electromagnetic steel sheet 40 due to curing shrinkage is reduced compared to the case where the adhesive portion 41 is provided on the entire surface. In addition, since the two-component SGA solidifies at room temperature, the stress caused by the difference in thermal expansion coefficient is also reduced. Therefore, the distortion of the electromagnetic steel sheet 40 can be suppressed, and the increase in iron loss can be suppressed.

[0087] The bonding portion 41 is partially provided between the electromagnetic steel sheets 40 adjacent to each other in the stacking direction. That is, in the electromagnetic steel sheet 40, a bonding area 42 and a non-bonding area 43 are formed on the surface (first surface) facing the stacking direction. The bonding area 42 is an area on the first surface of the electromagnetic steel sheet 40 where the bonding portion 41 is provided, that is, an area on the first surface of the electromagnetic steel sheet 40 where the adhesive that is not divided and cured is provided. The non-bonding area 43 is an area on the first surface of the electromagnetic steel sheet 40 where the bonding portion 41 is not provided, that is, an area on the first surface of the electromagnetic steel sheet 40 where the adhesive that is not divided and cured is not provided. Preferably, in the stator core 21, between the electromagnetic steel sheets 40 adjacent to each other in the stacking direction, the bonding portion 41 is partially provided between the core backs 22 and also partially provided between the teeth 23.

[0088] The bonding portions 41 are typically dispersedly disposed at a plurality of locations between all groups of electromagnetic steel sheets 40 adjacent to each other in the stacking direction. That is, all groups of electromagnetic steel sheets 40 adjacent to each other in the stacking direction are typically stacked with a plurality of bonding portions 41 disposed therebetween.

[0089] exist Figure 3 , an example of the arrangement pattern of the bonding portion 41 is shown. In this example, the plurality of bonding portions 41 are formed into circular dots. More specifically, in the core back 22, the plurality of bonding portions 41 are formed into dots with an average diameter of 12 mm at equal angle intervals along the circumference thereof. In each tooth portion 23, the plurality of bonding portions 41 are formed into dots with an average diameter of 8 mm in the radial direction.

[0090] The average diameter shown here is only an example. The average diameter of the dot-shaped bonding portion 41 in the core back 22 can be appropriately selected from the range of 2 mm to 20 mm, and the average diameter of the dot-shaped bonding portion 41 in each tooth portion 23 can be appropriately selected from the range of 2 mm to 15 mm. In addition, Figure 3 The formation pattern is merely an example, and the number, shape, and arrangement of the bonding portions 41 provided between the electromagnetic steel sheets 40 can be appropriately changed as needed.

[0091] The average diameter is obtained by measuring the diameter of the adhesive trace of the peeled adhesive portion 41 of the electromagnetic steel sheets 40 with a ruler. If the shape of the adhesive trace in plan view is not a perfect circle, the diameter is the diameter of the circumscribed circle (perfect circle) of the adhesive trace in plan view.

[0092] In addition, in this specification, "to" which shows a numerical range means that the numerical values ​​described before and after it are included as a lower limit and an upper limit.

[0093] The bonding area ratio of the bonding portion 41 to the electromagnetic steel sheet 40 between the electromagnetic steel sheets 40 is preferably 20 to 80%, more preferably 30 to 75%, and further preferably 40 to 70%. When the bonding area ratio of the electromagnetic steel sheet 40 is equal to or greater than the lower limit of the above range, the electromagnetic steel sheets 40 adjacent to each other in the stacking direction can be bonded with sufficient bonding strength, so that the core rigidity is excellent. When the bonding area ratio of the electromagnetic steel sheet 40 is equal to or less than the upper limit of the above range, the effect of suppressing the core iron loss is even better.

[0094] The bonding area ratio of the electromagnetic steel sheet 40 is a ratio of the area of ​​the region (bonding region 42 ) occupied by the bonding portion 41 on the first surface of the electromagnetic steel sheet 40 to the area of ​​the first surface of the electromagnetic steel sheet 40 .

[0095] The bonding area ratio of the bonding portion 41 to the core back 22 is preferably 50 to 80%, more preferably 60 to 80%, and even more preferably 70 to 80%, from the perspective of the balance between bonding strength and the effect of suppressing iron loss.

[0096] The bonding area ratio of the core back 22 is the ratio of the area of ​​the region (bonding region 42 ) occupied by the bonding portion 41 on the first surface of the core back 22 to the area of ​​the first surface of the core back 22 of the electromagnetic steel sheet 40 .

[0097] The bonding area ratio of the bonding portion 41 to the tooth portion 23 is preferably 20 to 50%, more preferably 20 to 40%, and even more preferably 20 to 30%, from the perspective of the balance between bonding strength and the effect of suppressing iron loss.

[0098] The bonding area ratio of the tooth portion 23 is a ratio of the area of ​​the region (bonding region 42 ) occupied by the bonding portion 41 on the first surface of the tooth portion 23 to the area of ​​the first surface of the electromagnetic steel sheet 40 .

[0099] In the present embodiment, the plurality of electromagnetic steel sheets forming one side of the rotor core 31 are fixed to each other by caulking (dowels). However, the plurality of electromagnetic steel sheets forming the rotor core 31 may have a stacked structure fixed by an adhesive similar to the stator core 21 .

[0100] Furthermore, the stator core 21 and the rotor core 31 and other laminated cores may be formed by so-called rotational lamination.

[0101] (SGA)

[0102] As described above, SGA contains an acrylic acid compound, an oxidizing agent, and a reducing agent. In addition, the SGA in this embodiment is a two-part type, consisting of two parts, a first part and a second part. A part of the acrylic acid compound and the oxidizing agent in the above-mentioned components are added to the first part, and the remaining part of the acrylic acid compound and the reducing agent are added to the second part. The oxidizing agent is all added to the first part, and is not added to the second part. The reducing agent is all added to the second part, and the reducing agent is not added to the first part.

[0103] The acrylic compound is a compound having a substituted or unsubstituted acryloyl group. Examples of the substituted or unsubstituted acryloyl group include a group represented by CH2=C(R)CO- (R represents a hydrogen atom, a methyl group, or an ethyl group).

[0104] Examples of the acrylic compound include acrylic monomers, acrylic oligomers, and acrylic macromonomers.

[0105] Examples of the acrylic monomer include (meth)acrylic acid, methyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycerol (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate and the like; 2,2-bis(4-methacryloyloxyphenyl)propane, 2,2-bis(4-methacryloylethoxyphenyl)propane, 2,2-bis(4-methacryloylpropoxyphenyl)propane, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(tri)acrylate, and dipentaerythritol hexa(meth)acrylate and the like.

[0106] Examples of the acrylic oligomer include reaction products of the above-mentioned acrylic monomers, nonylphenol ethylene oxide (EO)-modified acrylates, bisphenol AEO-modified diacrylates, isocyanuric acid EO-modified di- and triacrylates, trimethylolpropane EO-modified triacrylates, polybasic acid-modified acrylic oligomers, urethane acrylates, and polyester acrylates.

[0107] These acrylic compounds may be used alone or in combination of two or more.

[0108] As the acrylic compound, from the viewpoint of curing time and workability, at least one selected from the group consisting of methyl methacrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate is preferred.

[0109] The content of the acrylic compound in SGA is preferably 20 to 70% by mass, more preferably 30 to 60% by mass, relative to the total mass of SGA. When the content of the acrylic compound is within the above range, the adhesive strength is further improved.

[0110] The content of methyl methacrylate in the acrylic compound is preferably 0 to 50% by mass, more preferably 20 to 40% by mass, relative to the total mass of SGA. The content of phenoxyethyl methacrylate is preferably 0 to 50% by mass, more preferably 10 to 30% by mass, relative to the total mass of SGA. The content of 2-hydroxyethyl methacrylate is preferably 0 to 50% by mass, more preferably 0 to 20% by mass, relative to the total mass of SGA. The content of 2-hydroxypropyl methacrylate is preferably 0 to 50% by mass, more preferably 0 to 20% by mass, relative to the total mass of SGA. When the content of each compound is below the upper limit of the range, the operability is relatively good.

[0111] When at least one selected from the group consisting of 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate is contained, a three-dimensional structure is formed during curing, and the average tensile modulus is improved.

[0112] The content of at least one selected from the group consisting of 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate is preferably 10 to 70% by mass based on the total mass of the acrylic compound.

[0113] The ratio of the acrylic compound in the first agent in the total amount of the acrylic compound in SGA is, for example, 50 to 90% by mass.

[0114] When SGA contains two or more acrylic compounds, the components of the acrylic compounds in the first agent and the components of the acrylic compounds in the second agent may be the same as or different from each other.

[0115] Examples of the oxidizing agent include organic peroxides such as cumene hydroperoxide, benzoyl peroxide, and tert-butyl peroxybenzoate. These oxidizing agents may be used alone or in combination of two or more.

[0116] The content of the oxidant in SGA is preferably 0.5 to 10 parts by mass, more preferably 1 to 7 parts by mass, relative to 100 parts by mass of the acrylic compound. When the content of the oxidant is above the lower limit of the range, the curing speed is better. When the content of the oxidant is below the upper limit of the range, the storage stability is better.

[0117] Examples of the reducing agent include thiourea compounds such as methylenethiourea and tetramethylthiourea; metal complexes such as cobalt naphthenate, copper naphthenate, and vanadyl acetoacetate; and tertiary amines such as trimethylamine, tributylamine, and N,N-dimethyl-p-toluidine. Any one of these reducing agents may be used alone, or two or more may be used in combination.

[0118] The content of the reducing agent in SGA is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the acrylic compound. When the content of the reducing agent is above the lower limit of the range, the curing speed is better. When the content of the reducing agent is below the upper limit of the range, the storage stability is better.

[0119] Preferably, the SGA further comprises an elastomer.

[0120] Elastomers contribute to the improvement of viscosity, flow characteristics, and elasticity.

[0121] When the SGA contains an elastomer, the elastomer may be formulated in the first agent, the second agent, or both.

[0122] Examples of the elastomer include acrylonitrile-butadiene rubber (NBR), methyl methacrylate-butadiene-styrene copolymer (MBS), chlorosulfonated polyethylene, polybutadiene rubber, and polymethyl methacrylate, etc. These elastomers may be used alone or in combination of two or more.

[0123] As the elastomer, NBR is preferred in view of the elasticity of the cured product.

[0124] When SGA contains an elastomer, the content of the elastomer varies depending on the type and molecular weight of the elastomer, but is, for example, 1 to 30% by mass relative to the total mass of SGA.

[0125] When the elastomer contains NBR, the content of NBR is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, relative to the total mass of SGA. When the content of NBR is above the lower limit of the range, the bonding strength is better. When the content of NBR is below the upper limit of the range, the curing speed is better.

[0126] If necessary, SGA may contain a solvent such as acetone or toluene. When SGA contains a solvent, the solvent may be added to the first agent, the second agent, or both.

[0127] If necessary, SGA can further contain other components. When SGA contains other components, the other components can be formulated in the first dose, the second dose, or both.

[0128] Examples of other components include acidic phosphates such as monomethyl phosphate and diphenyl phosphate, photopolymerization initiators such as benzophenone and benzyl dimethyl ketal, fine powdered silica, paraffin wax, palm wax, lanolin and the like.

[0129] The content of other components in SGA is, for example, 0 to 10% by mass relative to the total mass of SGA.

[0130] The average tensile modulus of the SGA solidified product at room temperature (20 to 30° C.) is preferably 1500 to 5000 MPa, and more preferably 1500 to 4000 MPa. When the average tensile modulus of the solidified product, i.e., the average tensile modulus of the bonding portion 41, is above the lower limit of the range, the iron loss characteristics of the laminated core are excellent. When the average tensile modulus of the solidified product is below the upper limit of the range, the bonding strength of the laminated core is excellent.

[0131] Regarding the average tensile modulus of the cured product of SGA, a sample for measurement is prepared and measured by a resonance method. Specifically, the sample is obtained as follows: two electromagnetic steel sheets 40 are bonded together using an adhesive (SGA) that is the object of measurement, and the adhesive is cured to form a bonding portion 41. In accordance with JIS R1602: 1995, the average tensile modulus of the sample is measured by a resonance method. Then, the influence of the electromagnetic steel sheet 40 itself is removed from the average tensile modulus of the sample (measured value) by calculation, thereby obtaining the average tensile modulus of the bonding portion 41 alone.

[0132] The tensile modulus obtained from the sample in this way is equal to the average value of the entire laminated core, so this value is regarded as the average tensile modulus. The composition is set so that the average tensile modulus hardly changes at the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average tensile modulus can also be measured at the upper end of the laminated core and the cured adhesive portion 41.

[0133] The average tensile modulus of the cured product of SGA can be adjusted by the type, physical properties, molecular weight, addition amount, etc. of the elastomer. For example, there is a tendency that the average tensile modulus increases as the molecular weight of the elastomer decreases.

[0134] Generally, two-component and one-component SGAs are known. As two-component SGCs, as described above, two-component types are known, including a dual-main component type in which an acrylic compound is provided in both the first component and the second component, and a primer type in which an acrylic compound is provided in only one of the first component and the second component (an acrylic compound and an oxidizing agent are provided in the first component, and a reducing agent is provided in the second component; and an acrylic compound and a reducing agent are provided in the first component, and an oxidizing agent is provided in the second component).

[0135] Single-component SGA requires heating to cure. In contrast, dual-component SGA can cure at room temperature. In addition, dual-component SGA does not require strict adjustment of the mixing ratio compared to primer-type SGA.

[0136] In addition, generally, as adhesives that can be cured at room temperature, in addition to two-component SGA, two-component epoxy adhesives, anaerobic adhesives, and cyanoacrylate adhesives are also known.

[0137] Two-component SGA has a relatively fast curing speed but can reduce stress, so it is superior to other adhesives that can be cured at room temperature in terms of suppressing iron loss.

[0138] (Manufacturing method of stator core)

[0139] The stator core 21 can be manufactured, for example, by partially applying the first and second agents of SGA to a portion of the surface of the electromagnetic steel sheet 40 at room temperature, overlapping and crimping the electromagnetic steel sheet 40 onto another electromagnetic steel sheet 40 , and repeating the process of forming the bonding portion 41 .

[0140] When the applied first agent and second agent come into contact, SGA solidifies at room temperature to form the bonding portion 41. The first agent and the second agent are typically applied to the same position on the surface of the electromagnetic steel sheet 40. Alternatively, one of the first agent and the second agent may be applied first.

[0141] Below, use Figure 4 A method of manufacturing the stator core 21 will be described with reference to the manufacturing apparatus 100 shown.

[0142] First, the manufacturing device 100 is described. In the same manufacturing device 100, while the electromagnetic steel sheet P is fed from the steel coil C (steel hoop) in the direction of the arrow F, it is punched multiple times using dies assigned to each stage, so that it is gradually formed into the shape of the electromagnetic steel sheet 40, the first and second agents of SGA are applied to the positions corresponding to the lower surfaces of the second and subsequent electromagnetic steel sheets 40, and the punched electromagnetic steel sheets 40 are sequentially stacked and crimped.

[0143] like Figure 4 As shown, the manufacturing device 100 includes: a first-stage punching station 110 at a position closest to the winding C; a second-stage punching station 120, which is adjacently arranged at a downstream side along the conveying direction of the electromagnetic steel sheet P than the punching station 110; a first adhesive coating station 130, which is adjacently arranged at a downstream side than the punching station 120; and a second adhesive coating station 140, which is adjacently arranged at a downstream side than the first adhesive coating station 130.

[0144] The punching station 110 includes a female die 111 disposed below the electromagnetic steel sheet P and a male die 112 disposed above the electromagnetic steel sheet P.

[0145] The punching station 120 includes a female die 121 disposed below the electromagnetic steel sheet P and a male die 122 disposed above the electromagnetic steel sheet P.

[0146] The first adhesive applying station 130 and the second adhesive applying station 140 include applicators 131 and 141 , respectively. The applicators 131 and 141 include a plurality of syringes arranged according to the arrangement pattern of the adhesive portions 41 described above.

[0147] The manufacturing apparatus 100 further includes a laminating station 150 at a downstream position of the second adhesive application station 140. The laminating station 150 includes a holding member 151, an outer peripheral punching female die 152, an outer peripheral punching male die 153, and a spring 154.

[0148] The holding member 151 and the outer peripheral punching female die 152 are arranged below the electromagnetic steel sheet P. On the other hand, the outer peripheral punching male die 153 and the spring 154 are arranged above the electromagnetic steel sheet P.

[0149] In the manufacturing apparatus 100 having the above-described configuration, first, the electromagnetic steel sheet P is taken from the coil C along the Figure 4 Then, the electromagnetic steel sheet P is first subjected to a punching process at the punching station 110. Then, the electromagnetic steel sheet P is subjected to a punching process at the punching station 120. Through these punching processes, a material having Figure 3 The shape of the electromagnetic steel sheet 40 of the core back 22 and the plurality of teeth 23 is shown. However, since it is not completely blanked at this point in time, it proceeds to the next step in the direction of arrow F.

[0150] In the first adhesive coating station 130 of the next process, the first dose of SGA is supplied from the syringes of the coater 131, and the first dose is applied in dots to a plurality of locations on the lower surface of the electromagnetic steel sheet 40. In the second adhesive coating station 140 of the next process, the second dose of SGA is supplied from the syringes of the coater 141, and the second dose is applied in dots on the first dose applied in the first adhesive coating station 130.

[0151] Alternatively, the second adhesive may be applied in the first adhesive application station 130 , and the first adhesive may be applied in the second adhesive application station 140 .

[0152] Then, finally, the electromagnetic steel sheet P is sent to the stacking station 150, punched by the outer peripheral punching male die 153, and stacked with high precision. For example, by forming notches at multiple locations on the outer peripheral end of the core back and pressing a ruler into the notches from the side, it is possible to prevent the electromagnetic steel sheets 40 from shifting and stack them with higher precision. When stacking, the electromagnetic steel sheets 40 are subjected to a certain pressure from the spring 154.

[0153] By repeating the punching step, the first and second SGA coating steps, and the laminating step described above, a predetermined number of electromagnetic steel sheets 40 can be stacked. Furthermore, in the core formed by stacking the electromagnetic steel sheets 40 in this way, the SGA solidifies at room temperature to form the bonding portion 41.

[0154] Through the above steps, the stator core 21 is completed.

[0155] [Second embodiment]

[0156] Instead of SGA, an acrylic adhesive containing an acrylic compound other than SGA may be used to form the bonding portion. Examples of the acrylic adhesive other than SGA include anaerobic adhesives.

[0157] The rotating electrical machine of the second embodiment can be configured similarly to the first embodiment except that an anaerobic adhesive is used instead of the SGA.

[0158] In the second embodiment using the anaerobic adhesive, since the bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction, the stress applied to the electromagnetic steel sheet due to curing shrinkage is reduced compared to the case where the bonding portion is provided on the entire surface. In addition, since the anaerobic adhesive cures at room temperature, the stress caused by the difference in thermal expansion coefficient is also reduced. Therefore, the distortion of the electromagnetic steel sheet can be suppressed, and the increase in iron loss can be suppressed.

[0159] (Anaerobic adhesive)

[0160] Anaerobic adhesives are acrylic adhesives that start curing by shutting off oxygen in the presence of metal ions.

[0161] The anaerobic adhesive contains an acrylic compound, a polymerization initiator, and an anaerobic curing accelerator.

[0162] The acrylic compound contained in the anaerobic adhesive is not particularly limited, and examples thereof include H2C=CR 1 -COOR 2 However, in the above formula, R 1 is a hydrogen atom, a halogen atom or an alkyl group having 1 to 4 carbon atoms. 2 R is an alkyl group, cycloalkyl group, alkenyl group, cycloalkenyl group, alkaryl group, aralkyl group or aryl group having 1 to 16 carbon atoms. 2 The group may have a substituent such as a halogen atom, a hydroxyl group, or a carboxyl group, and may contain a divalent group such as a carbonyl group, an ester group, or an amide group.

[0163] Regarding the (meth)acrylate contained in the anaerobic adhesive, for example, methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, isobornyl acrylate, polyethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tetramethylene (meth)acrylate, ethyl (meth)diacrylate, and neopentyl glycol di(meth)acrylate can be exemplified. The (meth)acrylate contained in the anaerobic adhesive may be one kind or two or more kinds.

[0164] As the (meth)acrylate contained in the anaerobic adhesive, from the viewpoint of curing speed, one or more selected from the group consisting of di(meth)acrylates, ethyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate are preferred.

[0165] The content of the acrylic compound in the anaerobic adhesive is preferably 50 to 95% by mass, more preferably 70 to 90% by mass, based on the total mass of the anaerobic adhesive.

[0166] Examples of the polymerization initiator include hydroperoxides such as cumene hydroperoxide, tert-butyl hydroperoxide, p-methane hydroperoxide, methyl ethyl ketone peroxide, cyclohexane peroxide, diisopropylbenzene peroxide, and diisopropylbenzene hydroperoxide, and other organic peroxides such as ketone peroxides, diallyl peroxides, and peroxyesters.

[0167] As the polymerization initiator contained in the anaerobic adhesive, hydroperoxides are preferred from the viewpoint of storage stability (pot life).

[0168] The amount of the polymerization initiator is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the total mass of the acrylic compound. If it is less than 0.1 parts by mass, the polymerization reaction is insufficient, while if it is more than 5 parts by mass, the stability of the anaerobic adhesive decreases.

[0169] The anaerobic curing accelerator is not particularly limited, and examples thereof include toluidines such as N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, and N,N-diethyl-o-toluidine, saccharin, hydrazines such as acetylphenylhydrazine (APH), benzotriazole, ethyl mercaptan, maleic acid, naphtha, and anthraquinone. The anaerobic curing accelerator contained in the anaerobic adhesive may be one or more.

[0170] As the anaerobic curing accelerator contained in the anaerobic adhesive, benzotriazole, ethyl mercaptan, and hydrazines are preferred from the viewpoint of storage stability (pot life).

[0171] The content of the anaerobic curing accelerator in the anaerobic adhesive is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 1 part by mass, based on 100 parts by mass of the total mass of the acrylic compound.

[0172] For the same reason as for SGA, it is preferred that the anaerobic adhesive further contains an elastomer.

[0173] As the elastomer, the same elastomer as that exemplified in SGA can be exemplified. The elastomer included in the anaerobic adhesive can be either one or two or more. As the elastomer included in the anaerobic adhesive, NBR is preferred in terms of the elasticity of the cured product.

[0174] When the anaerobic adhesive contains an elastomer, the content of the elastomer varies depending on the type and molecular weight of the elastomer, but is, for example, 1 to 30% by mass relative to the total mass of the anaerobic adhesive.

[0175] When the elastomer contains NBR, the content of NBR is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, relative to the total mass of the anaerobic adhesive. When the content of NBR is above the lower limit of the range, the bonding strength is better. When the content of NBR is below the upper limit of the range, the curing speed is better.

[0176] The anaerobic adhesive may contain other components besides the acrylic compound, the anaerobic curing accelerator and the elastomer. Examples of other components include maleimide, a reactive diluent, a plasticizer, a polymerization inhibitor, a thickener, and a filler.

[0177] The content of other components in the anaerobic adhesive is, for example, 0 to 10% by mass relative to the total mass of the anaerobic adhesive.

[0178] When an anaerobic adhesive is used, for example, the stator bonded laminated core can be manufactured by partially applying the anaerobic adhesive to a portion of the surface of the electromagnetic steel sheet at room temperature, overlapping and pressing the sheet onto another electromagnetic steel sheet, and repeating the operation of forming the bonded portion. For example, the stator bonded laminated core can be manufactured using a manufacturing device of the same configuration as the manufacturing device 100 except that the second adhesive coating station 140 is not provided.

[0179] [Third Embodiment]

[0180] Instead of SGA, a cyanoacrylate adhesive (instant adhesive) containing cyanoacrylate may be used as the acrylic compound. The rotating electrical machine of the third embodiment can be similar to the first embodiment except that the cyanoacrylate adhesive is used instead of SGA.

[0181] In the third embodiment using a cyanoacrylate acrylic adhesive, since the bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction, the stress applied to the electromagnetic steel sheet due to curing shrinkage is reduced compared to the case where the bonding portion is provided on the entire surface. In addition, since the cyanoacrylate acrylic adhesive cures at room temperature, the stress caused by the difference in thermal expansion coefficient is also reduced. Therefore, the distortion of the electromagnetic steel sheet can be suppressed, and the increase in iron loss can be suppressed.

[0182] (Cyanoacrylate adhesive)

[0183] As the cyanoacrylate adhesive, any adhesive obtained by polymerizing and curing cyanoacrylate can be used without limitation. Examples of cyanoacrylates included in the cyanoacrylate adhesive include methyl cyanoacrylate, ethyl cyanoacrylate, methoxyethyl cyanoacrylate, butyl cyanoacrylate, and octyl cyanoacrylate. The cyanoacrylates included in the cyanoacrylate adhesive may be one or more.

[0184] As the cyanoacrylate-based adhesive, from the viewpoint of workability, it is preferred that ethyl cyanoacrylate be contained.

[0185] For the same reason as for SGA, it is preferred that the cyanoacrylate adhesive further contain an elastomer.

[0186] As the elastomer, the same elastomer as that exemplified in SGA can be exemplified. The elastomer included in the cyanoacrylate adhesive can be either one or two or more. As the elastomer included in the cyanoacrylate adhesive, NBR is preferred in terms of the elasticity of the cured product.

[0187] The content of the cyanoacrylate in the cyanoacrylate adhesive is preferably 50 to 95% by mass, more preferably 70 to 90% by mass, based on the total mass of the cyanoacrylate adhesive.

[0188] When the cyanoacrylate adhesive contains an elastomer, the content of the elastomer varies depending on the type and molecular weight of the elastomer, but is, for example, 1 to 30% by mass relative to the total mass of the cyanoacrylate adhesive.

[0189] When the elastomer contains NBR, the content of NBR is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, relative to the total mass of the cyanoacrylate adhesive. When the content of NBR is above the lower limit of the range, the bonding strength is better. When the content of NBR is below the upper limit of the range, the curing speed is better.

[0190] The cyanoacrylate adhesive may also contain other components besides cyanoacrylate and elastomer. As other components, for example, as a curing accelerator, amines can be exemplified. Amines are not particularly limited, and for example, toluidines such as N,N-dimethyl-p-toluidine and N,N-diethyl-p-toluidine can be exemplified. When a curing accelerator is used, the progress of the chemical reaction is greatly accelerated, so it is better to mix the curing accelerator with the cyanoacrylate adhesive just before using the adhesive on the laminated core.

[0191] The content of other components in the cyanoacrylate adhesive is, for example, 0 to 10% by mass relative to the total mass of the cyanoacrylate adhesive.

[0192] When a cyanoacrylate adhesive is used, for example, a bonded laminated core for a stator can be manufactured by partially applying a cyanoacrylate adhesive to a portion of the surface of an electromagnetic steel sheet at room temperature, overlapping and pressing the sheet onto another electromagnetic steel sheet, and repeating the operation of forming a bonded portion. For example, a manufacturing apparatus having the same configuration as the manufacturing apparatus 100 can be used to manufacture a bonded laminated core for a stator except that the second adhesive coating station 140 is not provided.

[0193] In addition, the technical scope of the present invention is not limited to the above-mentioned embodiment, and various changes can be made within the scope not departing from the gist of the present invention.

[0194] The shape of the stator core is not limited to the form shown in the above embodiment. Specifically, the outer diameter and inner diameter of the stator core, the stacking thickness, the number of slots, the circumferential and radial dimension ratio of the teeth, and the radial dimension ratio of the teeth and the back of the core can be arbitrarily designed according to the desired characteristics of the rotating electrical machine.

[0195] In the rotor of the above embodiment, two permanent magnets 32 form one magnetic pole, but the present invention is not limited thereto. For example, one permanent magnet 32 ​​may form one magnetic pole, or three or more permanent magnets 32 may form one magnetic pole.

[0196] In the above embodiment, a permanent magnet field type motor is described as an example of a rotating electrical machine. However, the structure of the rotating electrical machine is not limited to the following examples, and various known structures not shown below can be adopted.

[0197] In the above embodiment, a permanent magnet field type motor is used as an example of a rotating electrical machine, but the present invention is not limited thereto. For example, the rotating electrical machine may be a reluctance type motor or an electromagnetic field type motor (winding field type motor).

[0198] In the above embodiment, a synchronous motor is described as an example of an AC motor, but the present invention is not limited to this. For example, the rotating electrical machine may be an induction motor.

[0199] In the above-mentioned embodiment, an AC motor is taken as an example of a rotating electrical machine, but the present invention is not limited thereto. For example, the rotating electrical machine may be a DC motor.

[0200] In the above-mentioned embodiment, the electric motor is taken as an example of the rotating electrical machine, but the present invention is not limited thereto. For example, the rotating electrical machine may be a generator.

[0201] The stator core 21 may be used in a transformer instead of the rotating electrical machine 10. In this case, it is preferable to use a oriented electromagnetic steel sheet instead of a non-oriented electromagnetic steel sheet as the electromagnetic steel sheet.

[0202] In addition, the components in the above-described embodiments may be appropriately replaced with well-known components without departing from the gist of the present invention, and the above-described modifications may be appropriately combined.

[0203] Hereinafter, although the Examples of the present invention will be described in detail, the present invention is not limited to these Examples.

[0204] (Production Examples 1 to 5)

[0205] The first and second doses of SGA were prepared by mixing the components in the ratios shown in Table 1. Although not shown in the table, acetone was used as a solvent as appropriate.

[0206] (Production Examples 6 to 9)

[0207] The components were mixed in the ratios shown in Table 3 to prepare an anaerobic adhesive and a cyanoacrylate adhesive.

[0208] (Examples 1 to 6)

[0209] A steel hoop having a composition for a non-oriented electromagnetic steel sheet containing Si: 3.0 mass%, Al: 0.5 mass%, and Mn: 0.1 mass% was produced. The thickness of the steel base was 0.3 mm. An insulating coating treatment liquid containing a phosphate metal salt and an acrylic resin emulsion was applied to the ring material, baked at 300°C, and a predetermined amount of insulating coating was applied.

[0210] use Figure 4The manufacturing device 100 of the structure shown punches the steel hoop (electromagnetic steel plate) into a single-plate iron core in the following order. The single-plate iron core has an outer diameter of 300 mm and an inner diameter of 240 mm, and has 18 rectangular teeth with a length of 30 mm and a width of 15 mm on the inner diameter side. The single-plate iron core is stacked in sequence to produce a stator iron core.

[0211] The steel hoop is placed from the steel coil C along Figure 4 Then, the steel hoop is first subjected to a punching process at the punching station 110, and then to a punching process at the punching station 120. Through these punching processes, a steel hoop is formed with Figure 3 The shapes of the electromagnetic steel sheets 40 of the core back 22 and the plurality of teeth 23 are shown (punching process).

[0212] Next, in the first adhesive coating station 130, the first dose of SGA is dot-coated on multiple locations on the lower surface (first surface) of the steel hoop using the coater 131. Next, in the second adhesive coating station 140, the second dose is dot-coated on multiple locations on the lower surface of the steel hoop using the coater 141 (coating process). The first dose and the second dose are overlapped and coated on the same plane.

[0213] Next, the steel hoop sent to the laminating station 150 is punched out into a single plate core by the outer peripheral punching male die 153, and is laminated while being pressed (laminating step).

[0214] After repeating the above punching, coating and lamination steps to stack 130 single-plate cores, the laminated core discharged from the lower part of the mold is moved to a sample table prepared horizontally in the device and aged for 5 minutes in an atmosphere of 25°C to solidify the SGA and obtain a stator core.

[0215] In Examples 1 to 3, the bonding area ratios of the core back and the teeth were changed by changing the coating amounts of the first agent and the second agent. The electromagnetic steel sheets of the stator core obtained in each example were peeled off from each other, and the average diameter of the bonding portion, the core back, the teeth, and the bonding area ratios of the electromagnetic steel sheets were measured. The results are shown in Table 2.

[0216] (Examples 7 to 10)

[0217] Instead of using SGA, the anaerobic adhesive shown in Table 4 is used, and the average diameter of the bonding portion, the thickness of the bonding portion, and the bonding area ratio of the core back, the tooth portion, and the electromagnetic steel plate are shown in Table 4. A stator core is obtained in the same manner as in Example 1, except that pressure is applied and crimped after the anaerobic adhesive is applied to allow it to cure.

[0218] (Examples 11 to 14)

[0219] A stator core was obtained in the same manner as in Example 1 except that the cyanoacrylate adhesive shown in Table 4 was used instead of SGA, and the average diameter of the bonding portion, the thickness of the bonding portion, and the bonding area ratios of the core back, the tooth portion, and the electromagnetic steel sheet were shown in Table 4, and pressure bonding was performed after applying the cyanoacrylate adhesive to cure it.

[0220] (Comparative Example 1)

[0221] A stator core was produced in the same manner as in Example 1 except that the first and second doses of SGA were applied so that the bonding area ratio of the electromagnetic steel sheet was 100%.

[0222] (Comparative Example 2)

[0223] A stator core was produced in the same manner as in Example 1 except that the SGA of Manufacturing Example 4 was used as an adhesive.

[0224] (Comparative Example 3)

[0225] A stator core was produced in the same manner as in Example 1 except that a one-component thermosetting epoxy adhesive ("EP171" manufactured by Cemedine) was used as the adhesive.

[0226] (Comparative Example 4)

[0227] A stator core was produced in the same manner as in Example 7, except that the anaerobic adhesive shown in Table 4 was used instead of SGA, and the coating was performed so that the bonding area ratio of the electromagnetic steel sheet was 100%.

[0228] (Comparative Example 5)

[0229] A stator core was produced in the same manner as in Example 11 except that the cyanoacrylate adhesive shown in Table 4 was used instead of SGA and the coating was performed so that the bonding area ratio of the electromagnetic steel sheet was 100%.

[0230] (evaluate)

[0231] The following evaluations were performed on the stator cores of the respective examples. The results are shown in Tables 2 and 4.

[0232] <Iron loss>

[0233] The stator iron loss was measured using a rotating iron loss simulator having a rotor-shaped detector with a diameter of 239.5 mm. The rotating iron loss simulator is disclosed in the Japanese Institute of Electrical Engineers Research Committee Documents, RM-92-79, 1992.

[0234] In the evaluation of the iron loss of the stator core, the core used as the evaluation standard was formed with eight bonding parts on the back of the core, and a rivet with a diameter of 1.5 mm was formed in the center of all the teeth, and the number of layers of the rivet-fixed laminated core was 10. The rotating iron loss simulator was measured for the stator core and the riveted laminated core of each example, and the iron loss was evaluated according to the following criteria.

[0235] 1: Compared with the riveted laminated core, the magnetic properties are 20% better.

[0236] 2: The magnetic properties are good within a range of 15% or more and less than 20% compared to the riveted laminated core.

[0237] 3: The magnetic properties are good within a range of 10% or more and less than 15% compared to the riveted laminated core.

[0238] 4: The improvement in magnetic properties is more than 0% and less than 10% compared to the riveted laminated core.

[0239] 5: Compared with the riveted laminated core, no improvement in magnetic properties was found.

[0240] <Productivity>

[0241] In use Figure 4 When the manufacturing apparatus shown above manufactured the stator core at 150 spm (the number of electromagnetic steel sheets laminated in one minute was 150 sheets), the fixing condition of the stator core taken out from the mold was determined, and the productivity was evaluated according to the following criteria.

[0242] 1: The stator core can be manufactured without any problems.

[0243] 2: After being taken out from the mold, the stator core is manufactured by keeping it for several seconds to several minutes.

[0244] 3: After being taken out from the mold, the stator core is manufactured by pressing the stacked surface.

[0245] 4: During processing, the electromagnetic steel sheets are peeled off from each other or stacked distortedly.

[0246] 5: The electromagnetic steel sheets are not sufficiently fixed to each other.

[0247]

Table 1

[0248]

[0249]

Table 2

[0250]

[0251]

Table 3

[0252]

[0253]

Table 4

[0254]

[0255] Industrial Availability

[0256] According to the present invention, the iron loss of a rotating electric machine can be suppressed and the productivity of a bonded laminated core for a stator can be improved. Therefore, the present invention has great industrial applicability.

[0257] Description of Reference Numerals

[0258] 10 Rotating motor

[0259] 20 Stator

[0260] 21 Bonded laminated core for stator

[0261] 40 Electromagnetic steel plate

[0262] 41 Bonding

[0263] 42 Bonding area

[0264] 43 Non-bonded area

Claims

1. A bonded laminated core for a stator, comprising: A plurality of electromagnetic steel sheets are stacked one on another and both sides are covered with insulating films, and a bonding portion disposed between the electromagnetic steel sheets adjacent to each other in a stacking direction and bonding the electromagnetic steel sheets to each other; The plurality of electromagnetic steel sheets respectively include an annular core back and a plurality of teeth; All groups of the electromagnetic steel sheets adjacent to each other in the stacking direction are bonded by the bonding portion; The adhesive forming the bonding portion comprises an acrylic compound, an oxidizing agent, and a reducing agent, and is a two-part acrylic adhesive in which a portion of the acrylic compound and the oxidizing agent are mixed in a first part, and the remaining portion of the acrylic compound and the reducing agent are mixed in a second part; The acrylic compound comprises at least one selected from the group consisting of methyl methacrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; With respect to the total mass of the acrylic adhesive, the methyl methacrylate is 0 to 50 mass %, the phenoxyethyl methacrylate is 0 to 50 mass %, the 2-hydroxyethyl methacrylate is 0 to 50 mass %, the 2-hydroxypropyl methacrylate is 0 to 50 mass %, The bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction; The plurality of bonding portions are respectively formed into circular dot shapes; The bonding area ratio of the bonding portion to the electromagnetic steel plate is 40-70%; The bonding area ratio of the bonding portion to the back of the core is 50-80%; The bonding area ratio of the bonding portion to the tooth portion is 20-40%.

2. The bonded laminated core for a stator according to claim 1, wherein: The acrylic adhesive further includes an elastomer.

3. The bonded laminated core for a stator according to claim 2, wherein: The elastomer comprises acrylonitrile-butadiene rubber; The acrylonitrile-butadiene rubber is contained in an amount of 1 to 20% by mass based on the total mass of the acrylic adhesive.

4. A bonded laminated core for a stator, comprising: A plurality of electromagnetic steel sheets are stacked one on another and both sides are covered with insulating films, and a bonding portion disposed between the electromagnetic steel sheets adjacent to each other in a stacking direction and bonding the electromagnetic steel sheets to each other; The plurality of electromagnetic steel sheets respectively include an annular core back and a plurality of teeth; All groups of the electromagnetic steel sheets adjacent to each other in the stacking direction are bonded by the bonding portion; The adhesive forming the bonding portion is an acrylic adhesive containing an acrylic compound; The acrylic compound is cyanoacrylate, The acrylic adhesive further comprises an elastomer, The bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction; The plurality of bonding portions are respectively formed into circular dot shapes; The bonding area ratio of the bonding portion to the electromagnetic steel plate is 40-70%; The bonding area ratio of the bonding portion to the back of the core is 50-80%; The bonding area ratio of the bonding portion to the tooth portion is 20-40%.

5. The bonded laminated core for a stator according to claim 4, wherein: The elastomer comprises acrylonitrile-butadiene rubber; The acrylonitrile-butadiene rubber is contained in an amount of 1 to 20% by mass based on the total mass of the acrylic adhesive.

6. A bonded laminated core for a stator, comprising: A plurality of electromagnetic steel sheets are stacked one on another and both sides are covered with insulating films, and a bonding portion disposed between the electromagnetic steel sheets adjacent to each other in a stacking direction and bonding the electromagnetic steel sheets to each other; The plurality of electromagnetic steel sheets respectively include an annular core back and a plurality of teeth; All groups of the electromagnetic steel sheets adjacent to each other in the stacking direction are bonded by the bonding portion; The adhesive forming the bonding portion is an acrylic adhesive containing an acrylic compound; The acrylic adhesive is an anaerobic adhesive. The acrylic adhesive further comprises an elastomer, The bonding portion is partially provided between the electromagnetic steel sheets adjacent to each other in the stacking direction; The plurality of bonding portions are respectively formed into circular dot shapes; The bonding area ratio of the bonding portion to the electromagnetic steel plate is 40-70%; The bonding area ratio of the bonding portion to the back of the core is 50-80%; The bonding area ratio of the bonding portion to the tooth portion is 20-40%.

7. The bonded laminated core for a stator according to claim 6, wherein: The elastomer comprises acrylonitrile-butadiene rubber; The acrylonitrile-butadiene rubber is contained in an amount of 1 to 20% by mass based on the total mass of the acrylic adhesive.

8. The method for manufacturing a bonded laminated core for a stator according to claim 1, wherein: After applying the first and second agents of the acrylic adhesive to a portion of the surface of the electromagnetic steel sheet at room temperature, the adhesive is overlapped and pressure-bonded to another electromagnetic steel sheet, and the bonding portion is formed repeatedly.

9. The method for manufacturing a bonded laminated core for a stator according to claim 4 or 6, wherein: After applying the acrylic adhesive to a part of the surface of the electromagnetic steel sheet at room temperature, the sheet is overlapped and pressure-bonded to another electromagnetic steel sheet, and the bonding portion is formed repeatedly.

10. A rotating electric machine comprising the bonded laminated core for a stator according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Manufacturing method for rotor

    JP2017046442A

  • Laminated iron core having superior iron loss characteristics, and its manufacturing method

    JP2002151335A

  • Method of manufacturing lamination layer iron core and apparatus of manufacturing lamination layer iron core

    JP2018107852A

  • Method of producing laminated steel plate and device for producing the same

    US20180056629A1